Evaluation of the C-MAC Miller Video Laryngoscope Sizes 0 and 1 During Tracheal Intubation of Infants Less Than 10 kg. Issue 7 (July 2020) - Raimann, Florian J.; Cuca, Colleen E.; Kern, Detlev; Zacharowski, Kai; Rolle, Udo; Meininger, Dirk; Weber, Christian F.; Byhahn, Christian; Mutlak, Haitham
Abstract : Study Objective: Video laryngoscopy has primarily been developed to assist in difficult airways. Using video laryngoscopy in pediatric airway management is an up-and-coming topic. The aim of the presented study was to compare the intubation conditions obtained when using the C-MAC video laryngoscope with Miller blades sizes 0 and 1 for standard direct laryngoscopy and indirect laryngoscopy in children weighing less than 10 kg. Design: This was a prospective study. Setting: The study was performed in a university hospital. Patients: Following ethical approval, 86 infants weighing less than 10 kg and undergoing surgery under general anesthesia were studied prospectively. Intervention: Indirect and direct laryngoscopy either with C-MAC Miller blade size 0 or size 1. Measurements: First, direct laryngoscopy was performed, and the best obtained view was graded without looking at the video monitor. A second investigator blinded to the view obtained under direct laryngoscopy graded the laryngeal view on the video monitor. Time to intubation, intubation conditions, and intubation attempts were recorded. Results: In infants less than 10 kg, intubation conditions were excellent. There were no significant differences between the use of Miller blade 0 or 1 in reference to Cormack-Lehane grade, time to intubation, time to best view, or intubation attempts. Comparing direct and indirect intubation conditions using either Miller blade 0 or 1 revealed that the use of indirect laryngoscopy provided a significantly better view ( P < 0.05) of the vocal cords. In 3 infants weighing more than 8 kg, the Miller blade 0 was described as too short and narrow for intubation. Conclusions: Both devices allowed for an excellent visualization of the vocal cords.